A Case of an Unusual Clinical Course of Mitral Stenosis - Rostyslav M. Vitovskyi; Volodymyr V. Isaienko; Andrii R. Vitovskyi; Olena V. Satmari; Inna G. Yakovenko; Natalia I. Volkova (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. The stage 4 mitral stenosis is accompanied by atrial fibrillation which significantly worsens the prognosis due to the possibility of thromboembolic complications. However, sinus rhythm does not exclude the possibility of thrombosis which sometimes requires differential diagnosis with heart tumors.The aim. To present a case of unusual thrombus formation in a patient with significant mitral stenosis on the background of sinus rhythm and describe the specifics of determining indications for surgical intervention.Case report. Female patient K., 42 years old, who was admitted on January 12, 2023 to the National Amosov Institute of Cardiovascular Surgery, had been suffering from rheumatism for the past 20 years. In this case, the clinical course of mitral stenosis could be classified as stage 4, since there were signs of severe heart failure (shortness of breath on light exertion, peripheral edema, right-sided pleuritis, pulmonary thrombosis). However, the patient had sinus rhythm, which is more characteristic of the stage 3 mitral stenosis. The patient underwent mitral valve prosthetic surgery and removal of an unusual thrombus from the pulmonary valve cavity on January 23, 2023.Conclusions. The course of mitral stenosis, despite its thorough study, may have unusual clinical and instrumental manifestations, which requires differential diagnosis with heart tumors and other diseases. In some cases, the mechanism of thrombus formation can be extremely unusual, which can be a subject for discussion by cardiologists.